Evaluating consistency of stakeholder input into participatory GIS-based multiple criteria evaluation: a case study of ecotourism development in Kurdistan. Issue 9 (2nd September 2017) - Sarky, Sarook; Wright, Jim; Edwards, Mary
Abstract : Multiple criteria evaluation (MCE) is often used with GIS to identify suitable sites for multi-purpose development such as ecotourism. Typically, expert or stakeholder consultation is used to identify weights reflecting the relative importance of map layers representing different criteria. The objective of this study was to evaluate a new consultative approach to GIS-based MCE, using ecotourism development in Kurdistan, Iraq, as a case study. In an initial and follow-up consultation, stakeholders were asked not only to assess the relative importance of different map layers for ecotourism development, but also to identify specific sites suitable for ecotourism. Seventy-eight ecotourism destinations nominated by participants had significantly higher MCE scores than a set of 58 locations chosen without reference to stakeholders ( t -test = 21.16; p < 0.001). The approach thus provides a straightforward means of assessing the consistency of stakeholder input into MCE and could be adapted for use in other site suitability assessments.